2017
DOI: 10.1111/gwat.12506
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Methane Occurrences in Aquifers Overlying the Eagle Ford Shale Play, South Texas

Abstract: Assessing natural vs. anthropogenic sources of methane in drinking water aquifers is a critical issue in areas of shale oil and gas production. The objective of this study was to determine controls on methane occurrences in aquifers in the Eagle Ford Shale play footprint. A total of 110 water wells were tested for dissolved light alkanes, isotopes of methane, and major ions, mostly in the eastern section of the play. Multiple aquifers were sampled with approximately 47 samples from the Carrizo-Wilcox Aquifer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Methodology is similar to that used in Nicot et al (2017aNicot et al ( , 2017b. It is described in Appendix S2 and summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodology is similar to that used in Nicot et al (2017aNicot et al ( , 2017b. It is described in Appendix S2 and summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…Several research papers documented the initial state of knowledge on dissolved methane distribution in groundwater (Osborn et al 2011;Jackson et al 2013a;Molofsky et al 2013). These initial studies were quickly followed by others in Pennsylvania (Heisig and Scott 2013;Baldassare et al 2014;Darrah et al 2014;Wilson 2014;Siegel et al 2015Siegel et al , 2016Christian et al 2016) and elsewhere: Colorado (Li and Carlson 2014;Sherwood et al 2016), Fayetteville in Arkansas (Warner et al 2013), Bakken in North Dakota (McMahon et al 2015), Texas (Nicot et al 2015(Nicot et al , 2017a(Nicot et al , 2017bWen et al 2016), and Canada (Cheung et al 2010;Moritz et al 2015;Humez et al 2016). The source of the dissolved methane is sometimes clear, in particular when it is microbial (Warner et al 2013;McMahon et al 2015) but still the object of conflicting studies when mostly thermogenic, such as in Pennsylvania (Jackson et al 2013a;Molofsky et al 2013;Darrah et al 2014) or Texas (Darrah et al 2014;Wen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the environmental effects of hydrocarbon extraction in petroleum basins targeted for drilling, baseline groundwater quality has been evaluated using a multiple geochemical tracer approach (e.g., Molofsky et al ; Darrah et al , ; McMahon et al ; Nicot et al , , ). These studies have identified elevated levels of methane at concentrations up to its saturation point in shallow aquifers and revealed an association between methane and NaCl‐type waters, valley bottoms, faulting, and highly reducing aquifers (Warner et al ; Jackson et al ; Darrah et al , ; Harkness et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…To this point, although it has been nearly seven years since the initial Osborn et al () paper, there is still a dearth of published genuinely predrill, baseline datasets. Although the baseline studies that have been published are of great value, the majority of these studies did not start until after unconventional shale‐gas drilling had commenced in these areas (Molofsky et al ; Baldassare et al ; Siegel et al ; Darrah et al ; Humez et al ; Nicot et al ; Harkness et al ; Nicot et al , ). Thus, it remains uncertain if observations from those datasets actually represent the natural background.…”
Section: Introductionmentioning
confidence: 99%
“…The oil and gas industry exercises a number of precautionary measures to ensure that groundwater quality is not impacted by nature. Multiple reconnaissance efforts have recently evaluated groundwater quality throughout the Western Gulf Basin revealing elevated levels of biogenic and thermogenic natural gas [25,26]; benzene, toluene, ethylbenzene and xylene (BTEX) compounds [27]; and total organic carbon, and various organic solvents [24] in private and public water supply wells. However, these data are the first to evaluate the prevalence of organic and inorganic groundwater constituents within the context of community members' perceptions, providing unique insight into the relationship between residents and the UD industry operations.…”
Section: Introductionmentioning
confidence: 99%